Pengaruh Free Cash Flow, Investment Opportunity Set (IOS) dan Risiko Bisnis Terhadap Harga Saham Pada Sub Sektor Perbankan BUMN Yang Terdaftar di BEI Periode 2014-2018 - Retno Wulan (LPPM Universitas Adiwangsa Jambi, 2024)
The purpose of this research is to determine the effect of free cash flow, investment opportunity Set (IOS) and simultaneous business risk to the price of shares in the banking sub-sector of BUMN listed on the Indonesia Stock Exchange (IDX) period 2014-2018 and to Know the effect of free cash flow, investment opportunity Set (IOS) and business risk partially against the price of shares in the banking sub-sector of BUMN listed on the Indonesia Stock Exchange (IDX) period 2014-2018. This research used a multiple linear regression analysis tool used to figure out the direction of the relationship between the independen variable of the dependen variabel. Then, to answer the purpose of this research is used the F-test anf t-test and koefisien determinasi. BUMN Bank is a bank that is wholly capital derived from the wealth of the state that is separated and its establishment under its own law. The object used in this research is the banking sector of BUMN listed on the Indonesia Stock Exchange. The reason why researchers have the objects of public bank BUMN because of the majority of the existing shares owned by the government and STATE banks can be said as a bank capable of being the benchmark of the people. The variable rate of free cash flow has a regression coefficient with a positive direction of 0.111. If assuming another independent variable is constant, this means that any increase in the free cash flow rate by 1 unit will increase the share price by 1.11%. The investment opportunity Set (IOS) variable has a regression coefficient in the positive direction of 0.539. If assumed another independent variable is constant, this means that any increase in investment opportunity Set (IOS) of 1 unit will increase the stock price by 5.39%. The business risk variable has a regression coefficient with a positive direction of 0.098. If assumed another independent variable is constant, this means that any increase in business risk by 1 unit will then increase the share price by 0.98%. Free cash flow, investment opportunity Set (IOS) and business risk affect the price of the share because the value of F count is greater than the value of F table (2.266 > 3.24) by 29.8%, while the remainder of 70.2% is described or influenced by other variables Not researched. Free cash flow and business risk have no effect on the stock price, the investment opportunity set affects the price of the share.